Attitude toward psychiatry among interns in Egypt. Issue 1 (January 2018) - El-Giliny, Abdel-Hady; Hamdey, Ibrahem; Fawzy, Mohamed; Elwasify, Mohamed; Elwasify, Mahmoud; Barakat, Doaa
Abstract : Objective: Negative attitude toward psychiatry (ATP) and not choosing it as a career are prevalent among graduated medical students; however, the situation in Egypt is unknown. This study aims to estimate the ATP and its choice as a career and their associated factors in Egyptian interns. Participants and methods: A systematic random sample of 306 interns from two medical schools anonymously completed a questionnaire covering the ATP-30 scale, their choice of psychiatry as a career, and the possible associated factors. The reasons for choosing or not choosing psychiatry as a career were explored. Results: The mean total ATP score was 98. The majority of interns (77.8%) reported a positive ATP and 22.2% reported a negative/neutral attitude. More than one-fourth (25.5%) of interns declared choosing psychiatry as a career. The most common reason for choosing psychiatry as a career was personal interest/enjoyment. The most common reason for not choosing psychiatry as a career was bad reputation/stigmatization. The logistic regression analysis showed that the independent predictors of negative attitudes are being affiliated to Assiut University [adjusted odds ratio (AOR)=2.3]. The independent predictors of choosing psychiatry as a career are positive attitude (AOR=7.1) and previous history of mental illness (AOR=2.0). Conclusion: Overall attitudes toward mental illness and choosing psychiatry as a career among interns in the two medical schools were positive. A further study with interns from different institutions is needed to gain a detailed nationwide picture.